Ageing and inpatient hospital expenditures: A study of steepening - Alipour, Vahid (Med J Islam Repub Iran, 2018)
Background: Considering the health economics aspect, the effect of population aging on the growth of medical expenditures is of great importance. Thus, the aim of this study was to investigate the growth rate of inpatient hospital expenditures (IHE) of older age groups compared to younger age groups or testing of steepening hypothesis. Methods: In this descriptive-analytic study, monthly IHE data of insured patients from April 2011 to March 2014 was collected from Iran Health Insurance Organization database. The sample consisted of 297,145 patients who were selected using stratified random sampling among the patients insured by different health insurance funds. Using the Age-cut method, patients were classified into two main age groups: older than 60 and under 60 years old. The average IHE of the two groups and the growth rate of their expenditures were estimated. At the 95% significance level, the difference in average growth rate of IHE was tested between the two age groups using tstatistic in Stata (version 13.0) software. Results: The findings of this study revealed that per capita IHE for the older and younger groups was $469 and $399, respectively. The monthly average growth rate of IHE for the older (60-90 yrs.) and younger groups (30-59 yrs.) was 2.43% and 2.38%, respectively. The difference between the monthly average growth rate of the older and younger groups was not statistically significant (t = - 0.0332; P value = 0.9736). Conclusion: Our study results rejected the steepening hypothesis. The monthly average growth rates of IHE in both older and younger age groups have risen to a similar extent over the period of 36 months. Further research should focus on the inpatient hospital expenditures of younger age groups to explain the causes of their increased expenditures.